Response of growth, yield attributes and yield to the application of KNap and NAA in cowpea (Vigna unguiculata (L.) Walp.) (Bangladesh Journal of Botany, 2008)
Six concentrations each of KNap and NAA along with a control were tested on cowpea cv. Bari Falon- 2. Results showed that irrespective of treatment differences, dry matter of cowpea (Vigna unguiculata) increased during 60 to 105 DAS. Concentrations above 50 ppm NAA increased plant height. The dry matter and yield increased with the increasing of the concentrations of KNap and NAA up to 1250 and 50 ppm, respectively. No significant differences of dry matter accumulation, grain yield and almost all the yield attributes were observed in between 1250 ppm KNap and 50 ppm NAA. The highest values of dry matter/plant (54.52 g), pod length (13.15 cm), number of pods/plant (10.29), number of seeds/pod (10.61), 1000 seed weight (122 g), seed yield/plant (15.51 g), seed yield/ha (1630 kg) and harvest index (37.32 %) were obtained due to application of 1250 ppm KNap. Yield attributes had significantly positive correlation amongst them. Â  Key words: Cowpea, Vigna unguiculata, Plant height, Dry matter, Yield DOI = 10.3329/bjb.v36i2.1500 Bangladesh J. Bot. 36(2): 127-132, 2007 (December)